Use of medicinal plants for headache, and their potential implication in medication-overuse headache: Evidence from a population-based study in Nepal. (April 2021) - Sørnes, Elise Øien; Risal, Ajay; Manandhar, Kedar; Thomas, Hallie; Steiner, Timothy J; Linde, Mattias
Background: In Nepal, traditional treatment using medicinal plants is popular. Whereas medication-overuse headache is, by definition, caused by excessive use of acute headache medication, we hypothesized that medicinal plants, being pharmacologically active, were as likely a cause. Methods: We used data from a cross-sectional, nationwide population-based study, which enquired into headache and use of medicinal plants and allopathic medications. We searched the literature for pharmacodynamic actions of the medicinal plants. Results: Of 2100 participants, 1794 (85.4%) reported headache in the preceding year; 161 (7.7%) reported headache on ≥15 days/month, of whom 28 (17.4%) had used medicinal plants and 117 (72.7%) allopathic medication(s). Of 46 with probable medication-overuse headache, 87.0% (40/46) were using allopathic medication(s) and 13.0% (6/46) medicinal plants, a ratio of 6.7:1, higher than the overall ratio among those with headache of 4.9:1 (912/185). Of 60 plant species identified, 49 were pharmacodynamically active on the central nervous system, with various effects of likely relevance in medication-overuse headache causation. Conclusions: MPs are potentially a cause of medication-overuse headache, and not to be seen as innocent in this regard. Numbers presumptively affected in Nepal are low but not negligible. This pioneering project provides a starting point for further research to provide needed guidance on use of medicinal plants for headache.